The democratic legitimacy of business interest representation in the European Union: Normative implications of the logic of access - Pieter Bouwen (Max Planck Institute for Research on Collective Goods, 2003)
This paper studies the capacity of business interests to contribute to the democratic legitimacy of EU governance through participation in the EU policy-making process. Whereas the unbalanced participation of business as opposed to non-business interests in EU policy-making has been problematized, no research has been conducted regarding the unequal participation of different organizational forms of business interest representation (companies, associations and consultants). Here, first it is argued on the basis of a theory of access that this unequal participation has important repercussions because the different organizational forms do not have the same potential to contribute to the legitimacy of EU governance. The theoretical approach makes it possible to bridge the gap between the EU legitimacy debate and the literature on EU business interest representation by establishing a relationship between the new concept of access goods and the existing notions of input/output legitimacy. Second, an empirical investigation of business interest participation is undertaken in order to systematically assess the empirical relevance of the normative propositions and consequently to make inferences about the democratic legitimacy of business interest participation in the EU policy-making process.
Keywords: 330; Interessenvertretung; Interessenpolitik; EU-Politik; EU-Staaten